Incidence of cardiovascular disease in familial combined hyperlipidemia: A 15-year follow-up study. (January 2019) - Luijten, Jim; van Greevenbroek, Marleen M.J.; Schaper, Nicolaas C.; Meex, Steven J.R.; van der Steen, Caroline; Meijer, Lisanne J.; de Boer, Douwe; de Graaf, Jacqueline; Stehouwer, Coen D.A.; Brouwers, Martijn C.G.J.
Abstract: Background and aims: Familial combined hyperlipidemia (FCHL) is a complex dyslipidemia associated with premature cardiovascular disease (CVD). The present study was conducted to 1) determine the incidence of CVD in FCHL in this era of protocolled, primary prevention; and 2) examine whether cardiovascular risk estimation based on the Systemic Coronary Risk Estimation (SCORE) chart, as proposed in the 2016 ESC/EAS guidelines for the management of dyslipidemia, is justified in FCHL. Methods: FCHL patients, their normolipidemic (NL) relatives and spouses originally included in our baseline cohort in 1998–2005 (n = 596) were invited for a follow-up visit to determine the incidence of CVD, defined as (non-)fatal coronary artery disease, ischemic stroke and peripheral artery disease requiring invasive treatment. Results: Follow-up data (median: 15 years) was acquired for 85% of the original cohort. The cumulative incidence of CVD was significantly higher in FCHL patients than in spouses (23.6% versus 4.7%; hazard ratio (HR): 5.4, 95%CI: 2.0–14.6; HR after adjustment for risk factors included in SCORE: 4.7, 95%CI: 1.6–13.8), but not in NL relatives compared to spouses (5.8% versus 4.7%). The SCORE chart tended to overestimate CVD risk in the spouses (observed [O]/expected [E] ratio:0.2, p  = 0.01), but not in FCHL patients (O/E:1.3, p  = 0.50). Conclusions: Risk of primary CVD is still substantially increased in FCHL patients, despite preventive measures. The overestimation of CVD risk by the SCORE chart – a nowadays frequently observed phenomenon thanks to improved primary prevention – was not seen in FCHL. These results suggest that more aggressive treatment is justified to avoid excessive CVD in FCHL. Graphical abstract: Highlights: Three quarters of familial combined hyperlipidemia (FCHL) patients receive lipid lowering treatment. The 15-year incidence of cardiovascular disease is still very high in FCHL. The SCORE risk factors do not fully account for the increased risk in FCHL.